In-circuit Signal Analysis in the Development of Digital Devices in Vivado 2018 - Зубков, О. В.; Свид, І. В.; Мальцев, О. С.; Сайківська, Л. Ф. (Theoretical and Applied Aspects of Device Development on Microcontrollers and FPGAs, MC&FPGA-2019, 2019)
Considered the implementation of in-circuit analysis of logical signals in digital devices synthesized in Xilinx Field-Programmable Gate Array. Designed a digital control device streaming analog-to-digital converter. An analysis of the results of the analog-digital conversion was carried out and measures were taken to smooth out the false results of the conversion.
Keywords: analog-digital converter; Field-Programmable Gate Array; in-circuit debugging; Logic Analyzer; bus; clock signal